Perceptions of the value of competitive sport for persons with physical disabilities - Herbert, Blanche S.(Blanche Sylvia) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. in Human Movement Studies) -- University of Stellenbosch, 1997.